Pratylenchus zeae a causative agent of Corn Root Rot in Jiangsu Province of China - Hu, Yaojun (Plant disease, 2023)
Corn (Zea mays L.) plays an important role in China's cash crops, not only as food, but a vital raw material for animal husbandry and industry (Li et al. 2022). Pratylenchus zeae is one of the most damaging root-lesion nematodes (RLN) that can result in decreased yield and quality of crops (Liu et al. 2017). In September 2020, five root/soil samples were collected from the rhizosphere of corn (cv. Zhengdan 958), which had weak growth and root brown lesions in Chenzhou Village, Taolin Town, Donghai County, Lianyungang City, Jiangsu Province of China. Nematodes were extracted from the collected samples using the modified Baermann funnel method (Hooper et al. 2005). RLN were found in all samples, an average of 46 RLN per gram of root and 138 RLN per 100 cm3 of soil. The obtained RLN females were sterilized with 0.3% streptomycin sulfate and then inoculated on each carrot disks individually to obtain the purified population. RLN were examined by morphological and molecular characteristics to confirm the species indentification. The main morphological measurements of adult (n = 15) included body length = 524.7 μm (mean) ± 15.1 (standard deviation) (range = 490.7 to 543.6 μm), stylet = 15.2 μm ± 0.8 (14.2 to 16.8 μm), tail length = 30.3 μm ± 2.5 (26.3 to 35.3 μm), a = 25.6 ± 1.3 (24.4 to 29.3), b = 5.3 ± 0.3 (4.7 to 5.8), c = 17.4 ± 1.4 (14.9 to 19.3), two annules on the lip region. No males were found in the specimens. The morphological characters of this population are consistent with the description of P. zeae (Castillo and Vovlas, 2007). Furthermore, DNA was extracted from individual nematodes. The primers of TW81/AB28 and D2A/D3B (Subbotin et al. 2006) were used to amplified the rDNA-ITS region and rDNA 28S D2-D3 region, respectively. The purified PCR products were ligated into One step ZTOPO-Blunt/TA vector and transformed to Escherichia coli strain DH5α, and then sequenced by Sunya Biotechnology Co., Ltd (Henan, China). The obtained seqences were submitted to NCBI. The rDNA-ITS sequences (669 bp, GenBank Accession No: OP456372 and OP466367) exhibited 95.0% to 97.1% of identity with P. zeae sequences (KU198980 and KU198975). The obtained D2-D3 region of the 28S rDNA sequences (782 bp, OP441397 and OP448675) exhibited 99.7% to 100% identity with P. zeae sequences (EU130893 and KY424269). Consequently, both morphological and molecular data confirmed the identity of P. zeae. To further confirm reproduction on corn, single corn seeds (cv. Zhengdan 958) were sown in eight 2-liter pots filled with 1.8-liter of sterilized soil in greenhouse at 28°C. About 15 days after sowing, each pot with one corn plant with the same growth status was selected to inoculate with 1,000 mixed stage nematodes of P. zeae , Eight pots of uninoculated corn plants were used as controls. After 60 days, the inoculated plants were harvested and brown lesions were observed on roots. No symptoms and nematodes was detected in the control. An average number of RLN per pot was 3,752 in soil and 1,183 in roots were extracted, the reproduction factor (final population/initial population) was 4.94, indicating that P. zeae infects and reproduces well on this corn cultivar. P. zeae has only been reported on corn in Guangxi Province, southern in China(Fang et al. 1994). To our knowledge, this is the fist report of P. zeae infecting corn in Jiangsu Province, eastern in China. As P. zeae can cause great damage to corn, necessary measures should be taken to prevent the spread of P. zeae to other areas